A estética japonesa na cultura brasileira: reflexões a partir de um estudo etnofotográfico sobre a performance ritual da festa da Cerejeira de Garça-SP - Santos, Amilton Leonardo dos [UNESP]; Simões, Rosa Maria Araújo [UNESP] (My University, 2013)
Aiming to understand the Japanese aesthetic in Brazilian culture and to produce a photographic exhibition of artistic and ethnographic nature, we performed a symbolic exegesis of the ritual performance of Garça Cherry Festival - SP (Brazil). The event takes place annually and is held in memory and honor of oriental culture. The festival features various elements of Japanese culture through expressive forms such as dance, music, costumes, martial arts and cooking. Therefore, the study was based on the anthropology of performance and visual anthropology with regard to symbolic exegesis of the party and look artistic and ethnographic photographic records of the proceedings. Such procedures supported the realization of artistic display that contributed, in turn, in promoting the local culture to a wider audience, and, methodologically, have contributed in visual identification and interpretation of the cultural elements of the ceremony.
Keywords: The Cherry Blossom Festival; NipoBrazilian culture; Popular art; Visual antrhopology; Anthropology of performance